Analisis Efisiensi Penggunaan Faktor Produksi Usahatani Tembakau di Subak Sengguan, Desa Sukawati, Kecamatan Sukawati - I KADEK EDI SWARTIKA; DWI PUTRA DARMAWAN; IDA AYU LISTIA DEWI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2021)
Efficiency Analysis of The Use of Tobacco Farming Production Factors in Subak Sengguan, Sukawati Village, District of Sukawati This research was conducted in Subak Sengguan, Sukawati Village, Sukawati District, Gianyar Regency. Sengguan Subak is one of the subaks that produce tobacco in Sukawati Village, Sukawati District. As a subak that develops tobacco cultivation in Sukawati Village, Subak Sengguan produces the most tobacco in Sukawati Village. The purpose of this research is to determine the level of technical efficiency, economic efficiency, and price (allocative) efficiency in tobacco farming in Subak Sengguan, Sukawati Village, Sukawati District. The data was obtained by taking samples of 46 farmers of Subak Sengguan members. To analyze the level of technical efficiency, economic efficiency, and price (allocative), the study used the Cobb-Douglas stochastic frontier production function analysis with the MLE (Maximum Likelihood Estimation) method using seven variables. The results of this study show that farmers in Subak Sengguan are in productive efficiency (technical, economic, and price (allocative)) with a cut-off value of ?0,70 it means that tobacco farmers in Subak Sengguan are able to take good advantage of the production factors, even though they are not in the right optimal production. Achieving optimal production can be done by using various production factors efficiently and in accordance with the recommended use.